Performance of SAE 52100 steel grinding using MQL technique with pure and diluted oil - Moraes, Douglas Lyra de [UNESP]; Garcia, Mateus Vinicius [UNESP]; Lopes, Jose Claudio [UNESP]; Fonteque Ribeiro, Fernando Sabino; Sanchez, Luiz Eduardo de Angelo [UNESP]; Foschini, Cesar Renato [UNESP]; Mello, Hamilton Jose de [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2019)
Grinding is one of the highest dimensional accuracy machining processes in the industry. To obtain the smallest form and geometrical workpiece deviation, it is necessary to add cutting fluids as the aim of ensuring the tolerances established for this process, by reducing the machining temperature, due to its cooling capacity, facilitating the cutting by its capacity lubricant. Currently, it is known that together with conventional fluid, there are problems related to environmental pollution and damage to the operator's health. Some techniques have come up to alleviate these problems; one of them is the minimum quantity lubricant (MQL) that has been outstanding for obtaining results close to flood application. This technique has stood out concerning the surface integrity and geometric and dimensional precision of the machined workpiece since a smaller quantity of cutting fluid is directed precisely in the cutting region. However, the reduced cooling capacity of MQL has promoted the researches to perfect this technique. In this way, this research aims to analyze the consequences of the water addition in this method to minimize the probability of thermal damages in the workpiece when applied in the grinding of SAE 52100 steel which is widely used in the manufacture of bearings, shafts, blades, and various other components where there is a need for high hardness and high abrasion resistance. The analysis of the output parameters evaluated the performance of the technique: surface roughness (Ra), roundness error, diametrical wheel wear, viscosity, cutting power, metallography, and microhardness. Beyond this, it evaluated the behavior of each lubri-refrigeration method concerning the ground surface through scanning electron and confocal microscopy, and it used optical microscopy to analyze of the grinding wheel cutting surface. The results of the water increment in the MQL were superior to those of the MQL (oil-pure) in almost all aspects, remaining inferior only in the cutting power. Also, the 1:5 dilution (oil-water) presented close and satisfactory results when compared to traditional cutting fluid (flood); it becomes an excellent alternative for insertion environmentally correct cutting fluids in today's industry.
Keywords: Grinding; Flood technique; MQL technique; Cutting fluid diluted; SAE 52100 steel